Adipocyte Inflammation is Essential for Healthy Adipose Tissue Expansion and Remodeling - Asterholm, Ingrid Wernstedt (2014)
Chronic inflammation constitutes an important link between obesity and its pathophysiological sequelae. In contrast to the belief that inflammatory signals exert a fundamentally negative impact on metabolism, we show that pro-inflammatory signaling in the adipocyte is in fact required for proper adipose tissue remodeling and expansion. Three mouse models with an adipose tissue-specific reduction in pro-inflammatory potential were generated that display a reduced capacity for adipogenesis in vivo, while the differentiation potential is unaffected in vitro. Upon high fat diet exposure, the expansion of visceral adipose tissue is prominently affected. This is associated with decreased intestinal barrier function, increased hepatic steatosis and metabolic dysfunction. An impaired local pro-inflammatory response in the adipocyte leads to increased ectopic lipid accumulation, glucose intolerance and systemic inflammation. Adipose tissue inflammation is therefore an adaptive response that enables safe storage of excess nutrients and contributes to a visceral depot barrier that effectively filters gut-derived endotoxin.